Science Teacher Identity in Environmental Chemistry Education Using the STEM Approach: A Bibliometric Analysis of Scopus Journals (2015–2024) - Widyaningsih, Mia; Hernani, Hernani; Mudzakir, Ahmad; Supriatna, Asep; Kamaludin, Agus; Ragadhita, Risti (FKIP - Universitas Riau, 2025)
This study aims to investigate how Environmental Chemistry education contributes to shaping the science teacher identity of prospective chemistry teachers through a STEM approach. The bibliometric analysis method was conducted using Scopus data (2015–2024), analyzed with Biblioshiny and VOS Viewer. From an initial 483 documents, 418 relevant works comprising articles, books, and reviews were selected based on keywords such as